Research Progress of Isolated Carbonate Platform - Chen, Hao (International Journal of Natural Resources and Environmental Studies, 2025)
Isolated carbonate platforms represent a distinct category within the morphological classification of carbonate platforms. Investigating their evolutionary processes encompassing formation, development, and demise holds significant implications for reconstructing basin tectonic evolution, restoring paleogeography, paleo-oceanographic conditions, and paleoclimate, exploring organism-environment co-evolution, deciphering celestial orbital parameter variations, and guiding hydrocarbon source rock evaluation and reservoir development. This study systematically reviews the definition and classification of isolated platforms, establishing an idealized sedimentary facies model based on Wilson's standard facies zones and modern analogs from the Great Bahama Bank. Special emphasis is placed on elucidating controlling factors and methodological approaches governing platform evolution and termination, accompanied by critical assessments of their research significance and practical applications. Notably, isolated carbonate platform research has evolved from traditional qualitative field outcrop analyses to modern multi-method quantitative-semi-quantitative approaches. The emergence of 2D/3D digital geological technologies and numerical simulation models enables three-dimensional visualization of stratigraphic frameworks and facies distribution, facilitating precise geological investigations. Future research should integrate tectonic processes, eustatic fluctuations, and paleoclimatic contexts while prioritizing carbonate producers' response to environmental fluctuations during platform evolution.